Reform of the Law of Inheritance in Turkey and Tunisia - Muzaki, Kiki Adnan; Jahar, Asep Saepudin; Suma, Muhammad Amin (Universitas Islam Negeri Raden Intan Lampung, 2020)
This study examines the reform of the law of inheritance in Turkey and Tunisia. Both countries reinterpret the law of inheritance based on the current social context where the changes of social structure particularly related to gender issues encourage changes in its implementation. Applying the library research method, this study aims at comparing the law of inheritance in Turkey and Tunisia and illustrating that the Sharia law associated with social issues is adapted to and reinterpreted according to the needs of the people. As the result, the study draws some conclusion that Turkey grants equal inheritance rights to men and women, whereas Tunisia integrates the inheritance legal system described in the Quran with the social context. This happens due to the fact that Turkey has been subject to total secularisation and has caused a conflict with the opposition since the beginning of its formation. In the meantime, Tunisia has attempted to avoid a conflict with the traditionalists. To that end, in Tunisia the opinions of the Mālikī and Ḥanafī scholars followed by the majority of the people are adopted and used as a source to formulate the first draft of the civil law.